From Pandemic to Post-Pandemic Society: A Bibliometric Mapping of COVID-19’s Impact on Sociological Research (2019–2024) - Alpan Pratama; Susiyanto, Susiyanto; Fransiskus Novrianto Pakpahan; Fitria Yuliani (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The COVID-19 pandemic has profoundly transformed sociological research, necessitating a systematic analysis of its impact on social structures, inequalities, and digital adaptation; however, while bibliometric studies have examined pandemic-related research in public health and economics, few have focused on sociology, leaving a gap in understanding disciplinary shifts and emerging themes. This study addresses this gap by mapping the evolution of sociological research from the pandemic to the post-pandemic era (2019–2024) using bibliometric analysis to identify key trends, gaps, and intellectual foundations, employing data from 648 Scopus-indexed documents across four Asian countries analyzed through VOSviewer for co-citation and bibliographic coupling, which revealed thematic clusters and temporal trends. Key findings highlight dominant themes such as mental health, digital inequality, and educational adaptation, with Indonesia and Turkey as leading contributors, while psychological impacts and hybrid work systems emerged as critical areas, though marginalized populations remained underrepresented. The study underscores the need for inclusive digital policies, longitudinal mental health research, and ethical tech governance to address post-pandemic societal challenges, providing a foundation for future research to adopt cross-cultural and multidisciplinary approaches in navigating the complexities of post-pandemic sociological inquiry.